Mucosal leishmaniasis is associated with the Leishmania RNA virus and inappropriate cutaneous leishmaniasis treatment. - Fredy A Pazmiño; Marcela Parra-Muñoz; Carlos H Saavedra; Sandra Muvdi-Arenas; Clemencia Ovalle-Bracho; María C Echeverry (PLoS ONE, 2025)
Background Mucosal leishmaniasis (ML) is a severe clinical form of leishmaniasis that is characterized by the destruction of the nasal and/or the oral mucosae and appears as a late complication in 5% to 10% of cutaneous leishmaniasis (CL) cases produced by species belonging to Leishmania (Viannia) subgenus. Some strains of Leishmania spp. carry an RNA virus known as Leishmania RNA virus (LRV) that may contribute to the appearance of ML. Methods To examine the role of LRV type 1 (LRV1) as a risk factor associated with ML, a retrospective case-control study involving 103 patients was conducted. Cases were defined as patients with ML (n = 33), and controls corresponded to patients with CL and without mucosal lesions (n = 70). Clinical data were recorded from the patient's medical records. Cryopreserved biopsies were used to detect LRV1 and identify Leishmania species. Results The frequency of LRV1 in the 103 patients was 16.5% (95% CI,10.4-25.12) being higher in samples from cases [33.33% (95% CI,18.89-51.76) than from controls [8.57% (95% CI, 3.82-18.10)]. L. (V.) braziliensis was identified in 63.6% of cases and 55.7% of the controls. Multivariate logistic regression indicated that infection with Leishmania spp. carrying LRV1 (OR = 6.30; 95% CI,1.52-26.10, p = 0.011) acts as risk factors for ML occurrence, while the completed treatment for the cutaneous event decreases the risk of ML (OR = 0.039; 95% CI, 0.01-0.12, p < 0.0001). Conclusions Our data support the association between LRV1 and ML occurrence and emphasize the effect of completed treatment for CL in preventing ML.